Comprehensive analysis of the Lycopodium japonicum mitogenome reveals abundant tRNA genes and cis-spliced introns in Lycopodiaceae species - Sun, Ning; Han, Fuchuan; Wang, Suyan; Shen, Fei; Liu, Wei; Fan, Weishu; Bi, Changwei (Frontiers in Plant Science, 2024)
Lycophytes and ferns represent one of the earliest-diverging lineages of vascular plants, with the Lycopodiaceae family constituting the basal clade among lycophytes. In this research, we successfully assembled and annotated the complete Lycopodium japonicum Thunb. (L. japonicum) mitochondrial genome (mitogenome) utilizing PacBio HiFi sequencing data, resulting in a single circular molecule with a size of 454,458 bp. 64 unique genes were annotated altogether, including 34 protein-coding genes, 27 tRNAs and 3 rRNAs. It also contains 32 group Ⅱ introns, all of which undergo cis-splicing. We identified 195 simple sequence repeats, 1,948 dispersed repeats, and 92 tandem repeats in the L. japonicum mitogenome. Collinear analysis indicated that the mitogenomes of Lycopodiaceae are remarkably conserved compared to those of other vascular plants. We totally identified 326 RNA editing sites in 31 unique protein-coding genes with 299 sites converting cytosine to uracil and 27 sites the reverse. Notably, the L. japonicum mitogenome has small amounts foreign DNA from plastid or nuclear origin, accounting for only 2.81% of the mitogenome. The maximum likelihood phylogenetic analysis based on 23 diverse land plant mitogenomes and plastid genomes supports the basal position of lycophytes within vascular plants and they form a sister clade to all other vascular lineages, which is consistent with the PPG I classification system. As the first reported mitogenome of Lycopodioideae subfamily, this study enriches our understanding of Lycopodium mitogenomes, and sets the stage for future research on mitochondrial diversity and evolution within the lycophytes and ferns.